24.6k views
0 votes
If F(x) = 3x-2and g(x) = 2x+ 1,find (f-g)(x)

2 Answers

2 votes

Answer:

(f - g)(x) = x - 3

Explanation:

(f - g)(x) = f(x) - g(x)

We have f(x) = 3x - 2 and g(x) = 2x + 1. Substitute:

(f - g)(x) = (3x - 2) - (2x + 1)

(f - g)(x) = 3x - 2 - 2x - 1 combine like terms

(f - g)(x) = (3x - 2x) + (-2 - 1)

(f - g)(x) = x - 3

User Jakubka
by
5.4k points
3 votes
(F)3x-2(g)2x+1
Your subtracting to subtract the two x
(3x-2)-(2x+1)
The parenthesis is to know they are separate and not a negative number not subtract
ANSWER:x-3
User Paul Becotte
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.